Metabolic Activity of Invasive Apple Snails Negatively Affects the Survival of Native Benthic Snail in Mangrove - Jinling Liu; Caiying Zhang; Huixiu Yu; Zixin Fu; Huizhen Xie; Yiming Wang; Benliang Zhao; Qing Li; Kailin Kuang; Huanting Lin (Biology)
The golden apple snail (GAS, Pomacea canaliculata) has invaded mangrove forests. The effect of water contaminated by metabolic activity of GAS feeding on Acanthus ilicifolius (T1), Sonneratia apetala (T2), and without food (CK) on the native mangrove black helmet snail (BHS, Neritina pulligera) was investigated under salinity conditions. The GAS deteriorated saline water quality (2.5‰). DO contents in T1 and T2 approached zero at 9 d. Compared to CK, the contents of COD, total N, NH4+, NO3−, and total P of the contaminated water in T1 increased by 297%, 205%, 262%, 210%, and 518% after 9 d, while these indicators in T2 increased by 74%, 31%, 57%, 326%, and 154%, respectively. The LC50 of the contaminated water in T1 against the BHS reached 22.72%. The weight of the BHS exposed to the 100% contaminated water in T1 and T2 significantly decreased after exposure. The content of GPT of the BHS exposed to the 100%-contaminated water in T1 and T2 increased by 55% and 26%, while the MDA content increased by 38% and 34%. The 100%-contaminated water in T1 led to cell degeneration and incomplete structure in the hepatopancreas tissue of the BHS. The GAS feeding on holly mangroves can compete against native mangrove snails through water deterioration.